The efficiency of the Romanian horticultural sector in comparisons with other EU countries - Cornelia Alboiu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The purpose of the paper is to analyze the competitiveness of the Romanian horticultural sector in terms of production efficiency, using a few specific indicators such as land productivity, labour productivity, and share of costs in production. These indicators have been calculated on the basis of FADN (Farm Accountancy Data Network) at the level of other EU member states as well, to compare these with the Romanian horticultural sector. The results reveal a low efficiency of production in Romania as against the other investigated country, which denotes a reduced impact of CAP measures in the horticultural sector from Romania, a poorly organized chain and quite a low horticultural production integration in the food chain. Therefore, Romania's integration into the EU structures and the implementation of all CAP measures in this sector has not had the expected effect yet.
Keywords: Q10; Q19; 330; horticultural sector; competitiveness indicators; CAP